A REPORT OF TEXTBOOK ANALYSIS : (Scaffolding English for Junior High School Students) - Hijjatul Qamariah (Getsempena English Education Journal, 2016)
In this paper, the textbook of junior high school entitled Scaffolding: English for Junior High School Students is analyzed. To this end, types of syllabus containing in the book are firstly explored. Then, it is argued what types of syllabus is dominantly governed the textbook by examining the content, activities and tasks in the textbook. It is revealed that the textbook predominantly instructed by structural syllabus with an approach of genre-based syllabus. However, the book is lacked of communicative approach even though the activities designed are aimed at increasing communicative competence of the students. Finally, the suggestion is made for the perfection of the textbook. It is recommended that to be more communicative in teaching and learning language, teacher can manipulate some activities in the textbook to be more expressive and real. In addition, the translation in every instruction of the task is not a good point of this textbook. It is supposed to be the learners acquire it as they are emergent in the process of learning. It will be meaningful for the learners when they understand by themselves without any translation provided.